2015
DOI: 10.1007/s00411-014-0581-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of EBT2 and EBT3 films for proton dosimetry in the 4–20 MeV energy range

Abstract: Radiochromic films such as Gafchromic EBT2 or EBT3 films are widely used for dose determination in radiation therapy because they offer a superior spatial resolution compared to any other digital dosimetric 2D detector array. The possibility to detect steep dose gradients is not only attractive for intensity-modulated radiation therapy with photons but also for intensity-modulated proton therapy. Their characteristic dose rate-independent response makes radiochromic films also attractive for dose determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…Indeed, flatbed scanners show a reduced response at lateral positions perpendicular to the scanning direction depending on the optical density of the scanned film. When using these films in ion beams, the energy‐dependent dose response in the vicinity of the Bragg peak has to be considered . Since films have been considered with a primary goal of relative dosimetry, mainly to cross‐check transverse dose distributions against 2D‐arrays and scintillating screens, our commissioning work was mainly focused on the plateau part of the depth‐dose distribution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, flatbed scanners show a reduced response at lateral positions perpendicular to the scanning direction depending on the optical density of the scanned film. When using these films in ion beams, the energy‐dependent dose response in the vicinity of the Bragg peak has to be considered . Since films have been considered with a primary goal of relative dosimetry, mainly to cross‐check transverse dose distributions against 2D‐arrays and scintillating screens, our commissioning work was mainly focused on the plateau part of the depth‐dose distribution.…”
Section: Methodsmentioning
confidence: 99%
“…When using these films in ion beams, the energy-dependent dose response in the vicinity of the Bragg peak has to be considered. 39,40 Since films have been considered with a primary goal of relative dosimetry, mainly to cross-check transverse dose distributions against 2D-arrays and scintillating screens, our commissioning work was mainly focused on the plateau part of the depth-dose distribution. Films were calibrated in terms of dose to water using a 179.2 MeV proton beam by irradiating films with different dose levels between 0 and 5 Gy at 2 cm depth.…”
Section: B3 Equipment Dedicated To Lateral Dose Distributionsmentioning
confidence: 99%
“…Reinhardt et al. noted that as much as a 24% correction to the film response may be needed for proton energies lower than 11Mev while higher energies result in little change to the film response . The low‐energy proton response of EBT film from Kirby et al.…”
Section: Introductionmentioning
confidence: 99%
“…25 Reinhardt et al noted that as much as a 24% correction to the film response may be needed for proton energies lower than 11Mev while higher energies result in little change to the film response. 23 The low-energy proton response of EBT film from Kirby et al showed the change in efficiency is less than 10% for proton energies greater than 3.2 Mev. 20 The results from these previous studies suggest that careful consideration must be taken when calibrating film response in high linear energy transfer (LET) environments.…”
Section: Introductionmentioning
confidence: 99%
“…Calibration films were irradiated at 18, 20, and 23 cm while the chamber array was irradiated at nearly identical depths of 18, 20 and 24 cm. The LET dependence of radiochromic films has been thoroughly investigated [6,18,22,2633] and it has been established that the effect is highest for lower (< 11 MeV) proton energies [28]. However, for spot scanning beams, there may be a larger distribution of energies used to irradiate the PTV which could make accounting for LET corrections quite variable.…”
Section: Methodsmentioning
confidence: 99%